<span><span><span>s+12</span>+<span>3s</span></span>−8</span><span>=
<span><span><span><span>s+12</span>+<span>3s</span></span>+</span>−8
</span></span>Combine Like Terms<span>
<span><span><span>s+12</span>+<span>3s</span></span>+<span>−8</span></span></span><span>=
<span><span>(<span>s+<span>3s</span></span>)</span>+<span>(<span>12+<span>−8</span></span>)</span></span></span><span>=
<span><span>4s</span>+<span>4</span></span></span>
the starting point of the function is 0
Answer:
6
Step-by-step explanation:
The value of x is 72
Each side increased by 20%
Answer:
f(x) = 7
Step-by-step explanation:
we use the bottom equation (4x+3) because
1 > 0
so
4(1) +3 = 7